Factors Affecting the Financial Performance of the Samarinda City Regional Government - Suci Lestari; Imam Nazarudin Latif; Eka Yudhyani (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: This study aims to analyze the effect of the effectiveness ratio and efficiency ratio on the financial performance of the Samarinda City Regional Government, as well as to test whether the regional financial independence ratio plays a mediating variable in the relationship between the ratio of effectiveness and efficiency to financial performance. Design/Methodology/Approach: The research uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method using the SmartPLS application. The data used is secondary data in the form of a report on the realization of the Samarinda City Regional Budget for 2016-2024 obtained from the Regional Financial and Asset Management Agency (BPKAD) of Samarinda City. The variables analyzed included the effectiveness ratio, efficiency ratio, independence ratio, and regional financial performance. Findings: The results showed that: (1) the effectiveness ratio had a not significant effect on the independence ratio; (2) the efficiency ratio has a significant effect on the independence ratio; (3) the independence ratio has a significant effect on financial performance; (4) the effectiveness ratio has a significant effect on financial performance; (5) the efficiency ratio has a significant effect on financial performance; (6) the effectiveness ratio has a insignificant effect on financial performance through the independence ratio; and (7) the efficiency ratio has a significant effect on financial performance through the independence ratio. These findings confirm that fiscal efficiency and independence play an important role in strengthening regional financial performance. Research limitations/implications: This study is limited to one area, namely Samarinda City, so generalization of results to other regions needs to be done carefully. The observation period only covers 2016–2024 using APBD ratio data, so it has not accommodated non-financial factors as well as institutional and governance aspects that can also affect financial performance. In addition, the use of secondary data makes researchers dependent on the completeness and accuracy of local government financial statements. Practical implications: The results of the study provide implications for the Samarinda City Government and other local governments that improving spending efficiency and strengthening financial independence—for example through optimizing Regional Original Revenue (PAD) and reducing dependence on transfer funds—can drive better financial performance. Local governments need to design strategies to increase the effectiveness and efficiency of APBD management simultaneously, accompanied by policies to strengthen the independent income base, so that financial performance becomes more sustainable. Originality/value: This study provides novelty value by examining the mediating role of the independence ratio in the relationship between the ratio of effectiveness and efficiency to the financial performance of local governments in the context of Samarinda City with the latest data for the 2016–2024 period. The SEM-PLS approach used allows for simultaneous testing of direct and indirect relationships, thus providing a more comprehensive understanding of how effectiveness, efficiency, and fiscal independence interact in shaping the financial performance of local governments. Paper type: Research paper